2018
DOI: 10.1093/cid/ciy795
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Respiratory Symptoms and Lung Abnormalities Among People With a History of Tuberculosis in Uganda: A National Survey

Abstract: Among the general population of Uganda, ex-TB patients are at high risk of chronic cough, phlegm, chest pain, haemoptysis and chest x-ray abnormalities. A history of TB was a greater predictor of chronic respiratory problems than old age or smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This might have been influenced by factors known to affect interpretation of x-rays including patient rotation or radiographs being taken in expiration. (5) We did not have functional outcomes such as pulmonary function tests or 6-minute walk test (6MWT), and these would be important to include in a prospective J o u r n a l P r e -p r o o f study. However, it has previously been reported that the CXR score employed in this work correlates inversely with 6MWT and forced expiratory volume in 1 second (FEV1) and positively with the St George's Respiratory Questionnaire (SGRQ) score, indicating poorer quality of life [14].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have been influenced by factors known to affect interpretation of x-rays including patient rotation or radiographs being taken in expiration. (5) We did not have functional outcomes such as pulmonary function tests or 6-minute walk test (6MWT), and these would be important to include in a prospective J o u r n a l P r e -p r o o f study. However, it has previously been reported that the CXR score employed in this work correlates inversely with 6MWT and forced expiratory volume in 1 second (FEV1) and positively with the St George's Respiratory Questionnaire (SGRQ) score, indicating poorer quality of life [14].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, treated patients often have significant residual lung damage comprising persistent cavities, bronchiectasis and volume loss (including from pleural scarring) [2]. Tuberculosis is thus not only a cause of acute infectious mortality but also of chronic morbidity [3][4][5] and premature death from later complications. This has been increasingly appreciated recently with the first international symposium on post-tuberculosis lung disease being held in 2020 [6].…”
mentioning
confidence: 99%
“…Previous evidence indicated that for the greatest delays, patient outcomes were worse. DD in PTB may cause more severe damage to the lungs [31], therefore such patients are at a high risk of respiratory complications, such as bronchiectasis and hemoptysis, which may complicate anti-TB treatments and impede recovery [32][33][34]. Moreover, previous evidence also reported that DD was a major risk factor for TB-related death [35].…”
Section: Discussionmentioning
confidence: 99%
“…To date, much of the evidence about adverse health consequences post TB treatment has come from countries with a relatively low burden of TB (van Kampen et al, 2018a); there are limited data from high TB incidence settings. Population-based studies in Uganda ( van Kampen et al, 2018b) and South Africa (Hnizdo et al, 2000;Amaral et al, 2015;Buist et al, 2007;den Boon et al, 2007) have revealed a high burden of respiratory symptoms, chest X-ray abnormalities, and moderate to severe COPD, associated with a history of previous TB treatment. FTB patients constitute a large group (10/ 1000 population) in the adult population in several high TB burden communities in South Africa and also account for a considerable fraction of prevalent TB (19%) (den Boon et al, 2007;Marx et al, 2016aMarx et al, 2016a, suggesting opportunities for targeted TB control measures in this population (Marx et al, 2018).…”
Section: Introductionmentioning
confidence: 99%